In vitro Nutrient Digestibility and Fermentation Characteristics of King Grass Combined with Concentrate-Containing Mixed Microbes - Santoso, B.; Lekitoo, M.N.; Hariadi, B. Tj.; Widayati, T.W.; Abubakar, H. (Pakistan Journal of Nutrition, 2016)
The main feed for ruminants is forage, which is composed of polysaccharides. Feed digestion in the rumen is mediated by microbes, thus the type and makeup of rumen microbes are an important factor that affects nutrient digestibility. This study aimed to evaluate the in vitro nutrient digestibility and fermentation characteristics of king grass combined with a concentrate that contained mixed microbes. Lactobacillus plantarum, Saccharomyces cerevisiae and two strains of cellulolytic bacteria (i.e., Acinetobacter baumannii and Pseudomonas aeruginosa) were added to the concentrate. Cellulolytic bacteria were isolated from waste from either rice straw or palm oil seeds. The concentrate was mainly composed of agricultural and food industry wastes, such as cassava waste, tofu waste and rice bran. The following four concentrates were made: A, concentrate without microbe; B, concentrate containing L. plantarum and S. cerevisiae; C, concentrate containing L. plantarum, S. cerevisiae and P. aeruginosa and D, concentrate containing L. plantarum, S. cerevisiae and A. baumannii. Bacteria and yeast were added to the concentrate at 106-107 cfu/g. In vitro nutrient digestibility assays were conducted using 250 mg substrate composed of king grass and concentrate (70: 30, DM). Our findings revealed that concentrate contained 7.2 × 106 cfu/g L. plantarum, 3 × 108 cfu/g S. cerevisiae and 8.6 × 107 cfu/g A. baumannii and P. aeruginosa. The OM digestibility was greater (p<0.01) for the grass substrate with concentrate containing L. plantarum, S. cerevisiae and cellulolytic bacteria than for the concentrate that only contained L. plantarum and S. cerevisiae. Moreover, NDF digestibility was greater (p<0.01) for the grass substrate combined with concentrate that contained mixed microbes compared with the concentrate without microbes. The addition of cellulolytic bacteria increased NH3-N and acetic acid concentrations (p<0.05). We concluded that the addition of mixed microbes to the concentrate improved fermentation activity and the digestibility of nutrients in vitro.